PERAN MTV MTV EXIT DALAM MENINGKATKAN PUBLIC AWARENESS ANAK MUDA MENGENAI HUMAN TRAFFICKING DI INDONESIA PADA TAHUN 2012 - Arifin, Sarah Putri; Fasisaka, Idin; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT The increasing of human trafficking problem in Indonesia is an issue that needs to be addressed. This was the reason why MTV came out with their MTV EXIT Program or End Exploitation and Trafficking. the objective of this program was to raise the awareness of teenagers of how this issue mattered and how dangerous it could be. the approach was carried out by some methods that were easily accepted by teenagers such as concerts, documentary films, workshops, public service advertisements, and counseling to several cities and countries. The program took place in Indonesia from 2007 to 2014 as this country was one of the countries with the largest numbers of human trafficking cases. in 2012 MTV EXIT held a huge concert and roadshows to 3 cities that were known as places with highest numbers of cases. MTV EXIT hoped that teenagers at those 3 cities would be aware and put more attention to the human trafficking issue in Indonesia. Key words: MTV, MTV EXIT Program, Public Awareness, Human Trafficking, Indonesia